Reaction kinetics on model catalysts: Molecular beam methods and time-resolved vibrational spectroscopy - Libuda, Jörg (Surface Science, 2005)
Reaction kinetics on nanometer-scale particles are different from perfect single crystal surfaces. In heterogeneous catalysts this fact is empirically made use of in order to maximize the catalytic performance. Molecular beam experiments combined with vibrational spectroscopy on structurally well-defined model catalysts can provide detailed insight into the underlying reaction kinetics at the microscopic level. We critically review the recent developments, achievements and open questions of this approach. Scrutinizing simple test reactions, the application to various kinetic phenomena and their relevance for catalysis is discussed, including e.g., the role of the support and the identification of particle heterogeneities and specific reactive sites. It turns out that even for the simplest model catalysts, complex kinetic phenomena occur making the spectroscopic identification and monitoring of multiple coexisting reactant species one of the main challenges for future kinetic studies. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.reacti
Keywords: Carbon monoxide; Heterogeneous catalysis; IR reflection absorption spectroscopy; Methanol; Molecular beams; Nitrogen oxide; Palladium; Supported catalysts